All-in-one 2LabsToGo system for analysis of ergot alkaloids in whole rye - Jakob, Kevin; Schwack, Wolfgang; Morlock, Gertrud E.; Justus Liebig University Giessen (My University, 2024)
Ergot alkaloids, naturally occurring mycotoxins of Claviceps fungi, pose health risks. This necessitates accurate analysis methods to ensure food safety. This study explored the open-source miniaturized all-in-one 2LabsToGo system to analyze ergot alkaloids in whole rye samples. It is suited for sustainable atline analysis as it combines all planar chromatography tasks, allowing low-cost quality control in milling plants. The LOD and LOQ of ergocristine were determined to be 0.4 and 1.2 ng/zone, respectively. Detectability of ergot alkaloids was proven to be below the current maximum limit of 500 µg/kg for rye milling products. The repeatability (%RSD) was 4.1 % and the coefficient of determination of the analytical response (R2) was 0.9918 for ergocristine. The mean recovery rate of ergot alkaloids in spiked whole rye grain was close to 100 %. Results of screening whole rye for ergot alkaloids were successfully verified by comparison with those obtained by conventional status quo HPTLC instrumentation.